Multiplex blood group typing by cellular surface plasmon resonance imaging. Issue 2 (29th November 2018) - Szittner, Zoltan; Bentlage, Arthur E.H.; van der Donk, Eric; Ligthart, Peter C.; Lissenberg‐Thunnissen, Suzanne; van der Schoot, C. Ellen; Vidarsson, Gestur
Abstract : BACKGROUND: Blood‐group typing of donors and patients is essential to avoid incompatible transfusions. Transfusion of incompatible RBCs may result in alloimmunization complicating future transfusions or in the presence of antibodies in adverse reactions. With more than 300 blood group antigens identified, it is difficult to provide fully compatible blood. Currently, standard practice is to match for the most immunogenic antigens. While the current agglutination‐based RBC‐typing methods are reliable for testing a selected number of antigens, they are not easily adaptable for high‐throughput multiplex blood typing beyond the current standard. STUDY DESIGN AND METHODS: Surface plasmon resonance (SPR) is a label‐free method to follow molecular—and, very recently, also cellular—interactions in real time. Demonstration of binding of RBCs to blood group antigen‐specific antibodies by SPR has already been achieved. Here, we demonstrate the generation of an SPR array equipped with clinically relevant blood group antibodies (A, B, and Rh blood groups). To validate this method, we blindly compared typing of 946 blood donors with results of current diagnostic agglutination‐based methods. RESULTS: RBC typing was achieved by monitoring RBC binding to blood group–specific antibodies on the sensor simultaneously within 5 minutes per sample. Regeneration of the chip was robust, allowing for typing of at least 100 samples. The typing results gave a 100% match with classical serology with all antibodies tested besides anti‐E/e monoclonals, which gave inconsistent results due to low antibody specificity. CONCLUSION: This study demonstrates that SPR‐based RBC typing for multiple antigens can be realized simultaneously with high‐quality antibodies, enabling reduced hands‐on time and possibly improving cost efficiency.